A systems analysis of biodiesel production from wheat straw using oleaginous yeast: process design, mass and energy balances. Issue 1 (December 2016) - Karlsson, Hanna; Ahlgren, Serina; Sandgren, Mats; Passoth, Volkmar; Wallberg, Ola; Hansson, Per-Anders
Abstract Background Biodiesel is the main liquid biofuel in the EU and is currently mainly produced from vegetable oils. Alternative feedstocks are lignocellulosic materials, which provide several benefits compared with many existing feedstocks. This study examined a technical process and its mass and energy balances to gain a systems perspective of combined biodiesel (FAME) and biogas production from straw using oleaginous yeasts. Important process parameters with a determining impact on overall mass and energy balances were identified and evaluated. Results In the base case, 41% of energy in the biomass was converted to energy products, primary fossil fuel use was 0.37 MJprim /MJ produced and 5.74 MJ fossil fuels could be replaced per kg straw dry matter. The electricity and heat produced from burning the lignin were sufficient for process demands except in scenarios where the yeast was dried for lipid extraction. Using the residual yeast cell mass for biogas production greatly increased the energy yield, with biogas contributing 38% of total energy products. Conclusions In extraction methods without drying the yeast, increasing lipid yield and decreasing the residence time for lipid accumulation are important for the energy and mass balance. Changing the lipid extraction method from wet to dry makes the greatest change to the mass and energy balance. Bioreactor agitation and aeration for lipid accumulation and yeast propagation is energy demanding. Changes in sugar concentration in the hydrolysate and residence times for lipid accumulation greatly affect electricity demand, but have relatively small impacts on fossil energy use (NER) and energy yield (EE). The impact would probably be greater if externally produced electricity were used.